Metabolic and bariatric surgery: Postoperative management - Skelton, J; Murphy, A; Conradie-Smit, M; May, W (South African medical journal, 2025)
RECOMMENDATIONS 1. HCPs can encourage PLWO who have undergone MBS to participate in and maximise their access to behavioural interventions and allied health services at an MBS centre (Level 2a, Grade B). 2. We suggest that MBS centres communicate a comprehensive care plan to primary HCPs for patients who are discharged, including MBS procedure, emergency contact numbers, annual blood tests required, long-term vitamin and mineral supplements, medications, behavioural interventions, and when to refer back (Level 4, Grade D, Consensus). 3. We suggest that after a PLWO has been discharged from the MBS centre, HCPs should annually review nutritional intake, activity, compliance with multivitamin and mineral supplements and weight, as well as assess comorbidities, order laboratory tests to assess for nutritional deficiencies, and investigate abnormal results and treat as required (Level 4, Grade D, Consensus). 4. We suggest that HCPs consider referral back to the MBS centre or to a local bariatric medicine specialist for technical or gastrointestinal symptoms, nutritional issues, pregnancy, psychological support, weight regain, or other medical issues related to MBS as described in this chapter (Level 4, Grade D, Consensus). 5. We suggest that MBS centres provide appropriate follow-up and laboratory tests at regular intervals after surgery with access to appropriate HCPs (dietitian, nurse, social worker, surgeon, bariatric physician, psychologist/psychiatrist) until discharge/referral to primary care level is deemed appropriate for the patient (Level 4, Grade D, Consensus).